Cadherin-6 type 2, K-cadherin (CDH6) is regulated by mutant p53 in the fallopian tube but is not expressed in the ovarian surface - Karthikeyan, Subbulakshmi (Oncotarget, 2016)
High-grade serous ovarian cancer (HGSOC) is the most lethal gynecological malignancy and may arise in either the fallopian tube epithelium (FTE) or ovarian surface epithelium (OSE). A mutation in p53 is reported in 96% of HGSOC, most frequently at R273 and R248. The goal of this study was to identify specific gene targets in the FTE that are altered by mutant p53, but not in the OSE. Gene analysis revealed that both R273 and R248 mutant p53 reduces CDH6 expression in the oviduct, but CDH6 was not detected in murine OSE cells. p53(R273H) induced SLUG and FOXM1 while p53(R248W) did not induce SLUG and only modestly increased FOXM1, which correlated with less migration as compared to p53(R273H). An oviduct specific PAX8(Cre/+)/p53(R270H/+) mouse model was created and confirmed that in vivo mutant p53 repressed CDH6 but was not sufficient to stabilize p53 expression alone. Overexpression of mutant p53 in the p53 null OVCAR5 cells decreased CDH6 levels indicating this was a gain-of-function. SLUG knockdown in murine oviductal cells with p53(R273H) restored CDH6 repression and a ChIP analysis revealed direct binding of mutant p53 on the CDH6 promoter. NSC59984, a small molecule that degrades mutant p53(R273H), rescued CDH6 expression. In summary, CDH6 is expressed in the oviduct, but not the ovary, and is repressed by mutant p53. CDH6 expression with further validations may aide in establishing markers that inform upon the cell of origin of high grade serous tumors.